The drivers of profitability in the top 30 major airlines worldwide - Lopes, I. T. (2016)
Purpose: The main objective of the current research is to identify the impact of human and structural capital on profitability of major airlines and examine whether region, capital ownership and control, and strategic alliances, play a clustering effect on profitability. Design/methodology/approach: Using information from the top 30 airlines worldwide, in particular human and structural capital proxies, a linear model is regressed. Test of hypotheses were performed towards the identification of the influence emerged from variables such as Region, Capital ownership and control, and Strategic Alliances, on intellectual capital drivers and profitability. Findings: Turnover is driven by human and structural capital factors, namely: Employee Expenses and Benefits; Size of Board of Directors; Intangible Assets; Codeshare Agreements; and Passenger Traffic. Airlines profitability does not depend from region, capital ownership and control, or strategic alliance group in which the airline is integrated. Research limitations: In spite of the limitations, we underline the range of time under analysis and the sample size. However, the current approach can be replicated over time and based in other rankings, structured on different metrics and approaches. Practical implications: The empirical results provide both an understanding of how independent variables affect the performance of airlines and offer some explanation as to the relationship between key characteristics of firms and profitability. Originality: The research adds value to the current literature by exploring the effects of new intellectual capital drivers on profitability of airlines firms. Focused on a sector that strongly contributes to improve the networking between nations, it provides a new and updated overview.